2019
DOI: 10.2147/ott.s196914
|View full text |Cite
|
Sign up to set email alerts
|

<p>A novel curcumin derivative CL-6 exerts antitumor effect in human gastric cancer cells by inducing apoptosis through Hippo&ndash;YAP signaling pathway</p>

Abstract: Purpose Gastric carcinoma is the second most frequently diagnosed cancer and leading cause of cancer death in China. As a new generation of cancer therapeutic drug, CL-6, a curcumin derivative, shows better bioavailability than curcumin, which has shown anticancer effects in gastric cancer (GC). However, whether CL-6 shows similar activities in GC has not been examined. Materials and methods Cell proliferation assay, colony-forming assay, flow cytometric analysis, wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Curcumin is one such example which exhibits anti-cancer activity against various cancer types [4247]. Curcumin has been replaced by more potent and bioavailable derivatives, which have attracted attention for the development of novel drugs [48]. The novel curcumin derivatives developed in this study has exhibited remarkable cytotoxicity (~ 100X) better than parent compound at nanomolar concentrations on a wide range of cancer cell lines which includes both representative liquid and solid tumour cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is one such example which exhibits anti-cancer activity against various cancer types [4247]. Curcumin has been replaced by more potent and bioavailable derivatives, which have attracted attention for the development of novel drugs [48]. The novel curcumin derivatives developed in this study has exhibited remarkable cytotoxicity (~ 100X) better than parent compound at nanomolar concentrations on a wide range of cancer cell lines which includes both representative liquid and solid tumour cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…258 Further studies have confirmed the effects of curcumin on the Wnt/β-catenin and Hippo/YAP signaling pathways, inhibiting stemness or proliferation in multiple cancers. [259][260][261][262][263][264][265] Although limited bioavailability and stability hamper the application of curcumin in clinical cancer therapy, [266][267][268] curcumin has been used for treating patients with pancreatic cancer in clinical trials due to its anticancer activity and safety profile. 269,270 Drug repurposing of curcumin could prove beneficial for clinical translation using highly bioavailable forms of curcumin (e.g., micro-and nano-formulations of curcumin with greatly enhanced absorption) to target telomerase.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…In gastric cancer, YAP reduces apoptosis by promoting mitophagy downstream of SIRT1 activity, MFN2 expression, and upregulation of growth factors, whereas the targeting of YAP increases apoptosis [143][144][145]. In clear cell renal cell carcinoma [146] and rhabdomyosarcoma [147], YAP is upregulated, and YAP depletion increases apoptosis and decreases proliferation, even in murine xenografts in vivo.…”
Section: Cancer Types Where Yap Reduces Apoptosismentioning
confidence: 99%